The shifting reception of Jean-Paul Sartre in the People's Republic of China during the Cold War: A case study of the journal Shijie Wenxue (1953-1991) - Liu, Yingmei; Baer, Brian (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2025)
This research investigates the reception of French philosopher Jean-Paul Sartre in the People’s Republic of China (PRC) during the Cold War by focusing on the journal Shijie Wenxue, which was the only journal to publish translations under the PRC’s Communist regime until 1978. The article analyses the selection and de-selection of Sartre’s works for translation and publication in this journal, the triangulated translation of Sartre’s play La Putain respectueuse [The Respectful Prostitute] and the paratextual framing of Sartre and his works. This research adopts Lefevere’s (1992) theory of ideology and patronage, critical discourse analysis (CDA) and Baker’s (2016) narrative theory as theoretical frameworks. The researchers found ideology and politics influenced the reception of Sartre’s works in the PRC. We did not detect any translations or introductory articles which ran counter to the meta-narratives of the PRC during the Cold War. Instead, it was found that the actors (translators and editors) used a reframing strategy that involved adding an introductory text to the Chinese translations and further manipulating the texts, such as changing the ending of the stories, in order to enhance certain narratives while foreclosing others. The researchers also found that the public narratives on Sartre in the PRC underwent several shifts during this period.